Bioactive lipids in : implications for functional foods and health - Pais, Rita (2024)
Dunaliella salina is a green microalga extensively explored for β-carotene production, while knowledge of its lipid composition is still limited and poorly investigated. Among lipids, polar lipids have been highlighted as bioactive phytochemicals with health-promoting properties. This research aimed to provide an in-depth lipidome profiling of using liquid and gas chromatography coupled with mass spectrometry. The lipid content was 6.8%, including phospholipids, glycolipids, betaine lipids, sphingolipids, triglycerides, diglycerides, and pigments. Among the total esterified fatty acids, 13.6% were 18:3 omega-3 and 14.7% were 18:1 omega-9. The lipid extract of showed anti-inflammatory activity by inhibiting cyclooxygenase-2 activity at 100 µg/mL, dose-dependent antioxidant scavenging activity, and antidiabetic activity by inhibiting α-glucosidase activity at 25 and 125 µg/mL. In conclusion, the lipid extract of has the potential to be used as a functional food ingredient or in the nutraceutical and cosmeceutical industries.